Al3+ doping effects and high-field phase diagram of La0.5Sr0.5Mn1−xAlxO3. (2nd December 2015) - Shang, C; Xia, Z C; Wei, M; Jin, Z; Chen, B R; Shi, L R; Ouyang, Z W; Huang, S; Xiao, G L
Abstract: Magnetization measurements of La0.5 Sr0.5 Mn1− x Al x O3 (0  ⩽   x   ⩽  0.25) under pulsed high magnetic fields up to 50 T have been carried out, in which the Al 3+ ions doping and magnetic field effects on the charge-ordering/antiferromagnetic to ferromagnetic phase transitions have been discussed. A triple-phase diagram with the critical field, doping level and temperature has been determined, in which the antiferromagntic and ferromagnetic phase boundaries were clearly defined. The change from long-range charge-ordered/antiferromagnetic phases to the robust short-range ones upon the Al 3+ -doping was observed. According to the experimental results, we assume that Al 3+ ion doping at the Mn sites dilutes the Mn 3+ -O-Mn 4+ network, weakens the double-exchange interaction and further suppresses the FM phase (metallic conduction), which leads to the critical magnetic fields destroying the antiferromagnetic order increase with the increase of the doping level.